Global currents, local tides: An examination of the dynamic interplay between global value chains and local food markets - Ellen Mangnus; Marc Wegerif (Research in Globalization, 2025)
This article contributes to a special issue critically examining the shift from an "international" to a "global" development paradigm. Focusing on global value chains, the paper critiques the convergence-divergence thesis of Horner and Hulme (2019), which posits that globalization leads to converging development trends across countries but diverging inequalities within them. The article argues for a more in-depth examination of how local contexts, market practices, and actors interact with global dynamics. Through a narrative review, the paper traces the evolution of global value chains-from a framework for analysing transnational supply chains to a development tool-and critiques its limitations in addressing the complex inequalities that emerge both within and between countries. Focusing on food production, trade, and consumption, the article proposes a practice-based approach to globalization that more effectively captures the dynamics of global-local interactions and offers a nuanced understanding of how people shape-and are shaped by-globalization in their daily lives.
Keywords: 330; Development; Global Value Chains; Practice based approach